2022
DOI: 10.1155/2022/7138012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Reproductive Performance of Freshwater Finfish Species through Dietary Lipids

Abstract: Dietary lipid manipulation in the feed of commercially cultured finfish is used not only to improve production and culture but also to enhance their reproductive performances. The inclusion of lipid in broodstock diet positively affects growth, immunological responses, gonadogenesis, and larval survival. In this review, existing literature on the importance of freshwater finfish species to aquaculture and the inclusion of dietary lipid compounds in freshwater fish feed to accelerate the reproduction rate is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 106 publications
(171 reference statements)
1
2
0
Order By: Relevance
“…Secondly, the variation in fecundity could also be explained by the size and age of the females, where larger females present greater fecundity. Several studies have reported that the number of eggs produced by a female increases with size [3,[47][48][49]. In the present study, a high correlation was found between fecundity and weight among females, but not length; thus, heavier females produced more eggs compared to lighter females.…”
Section: Discussionsupporting
confidence: 55%
“…Secondly, the variation in fecundity could also be explained by the size and age of the females, where larger females present greater fecundity. Several studies have reported that the number of eggs produced by a female increases with size [3,[47][48][49]. In the present study, a high correlation was found between fecundity and weight among females, but not length; thus, heavier females produced more eggs compared to lighter females.…”
Section: Discussionsupporting
confidence: 55%
“…This observation could indicate a negative effect of higher DFR on the GSI. The amount of feed may affect the reproductive performance of the fish, which is an important factor in aquaculture (Izquierdo et al 2001;Torsabo et al 2022).…”
Section: Physiology and Fish Conditionmentioning
confidence: 99%
“…6 Furthermore, the demand for fish oil as fish feed is expected to exhibit a compound annual growth rate (CAGR) of approximately 5.2% from 2021 to 2028. 7 Hence, scientists have assessed the impacts of substituting fish oil with a combination of Schizochytrium sp. and Microchloropsis gaditana, including camelina oil, on the growth and efficiency of fish feed utilization.…”
Section: Introductionmentioning
confidence: 99%